Community Service Application of Puzzle Straw Teaching Aids in Mathematics Learning at Coastal Elementary School in Silo Baru Village Dusun X - Pulungan, Putri Su’aidah; Marpaung, Agus Salim (Center of Knowledge : Jurnal Pendidikan Dan Pengabdian Masyarakat, 2024)
This community service (PKM) activity aims to overcome the problems experienced by teachers at Pesisir Elementary School. new silo village, X hamlet, Silo Laut District, Asahan Regency. Namely the difficulty of teachers in cultivating students' interest in studying mathematics and the lack of a fun learning approach, one of which is the use of the Puzzle Straw mathematics props. Mathematical Straw Puzzles are puzzles that involve arranging straws to complete a challenge or achieve a certain goal. This can be a creative and fun form of puzzle or game involving the manipulation or arrangement of straws. This service activity was attended by 6 Pesisir Elementary School teachers. The results of this PKM activity are: 1) Students are more enthusiastic in learning mathematics, especially in geometric geometric material. This is because the Puzzle Straw teaching aid allows students to directly explore geometric concepts of geometric shapes. Students not only sit and listen to the teacher's explanation, but can also see directly all the objects in the props, carry out gradual exploration, and demonstrate the physical objects of the props. 2) Teachers' enthusiasm for responding to PKM program material has increased. This is indicated by the number of teachers asking questions, suggestions and criticism, as well as providing solution views on the application of Puzzle Straw teaching aids in elementary schools. 3) There has been a significant increase in teachers' knowledge and understanding of elementary school mathematics concepts, as well as the benefits of the Puzzle Straw teaching aids in elementary school mathematics learning, especially the concept of spatial geometry. This can be seen from the number of teachers who can answer questions about elementary school mathematics concepts, and can explain the benefits of the Puzzle Straw teaching aids in elementary school mathematics learning.